Optimization of the compression-based piezoelectric traffic model (CPTM) for road energy harvesting application - Gareh S.; Kok B.C.; Yee M.H.; Borhana A.A.; Alswed S.K. (International Journal of Renewable Energy Research, 2023)
Cellular automata; Degrees of freedom (mechanics); Electric power generation; Energy harvesting; Piezoelectricity; Roads and streets; Vehicles; 2DOF; Arrival rates; Cellular automaton; Cellular automatons; Cymbal transducer; Mean arrival rate; Piezoelectric; Piezoelectric cymbal transducer; Piezoelectric energy harvesters; Traffic modeling; Piezoelectric ceramics